Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1017/s0008413100017928
|View full text |Cite
|
Sign up to set email alerts
|

Control and Thematic Agreement

Abstract: In this article it is shown that Persian has core control constructions in which the obligatorily empty subject of an embedded clause takes its reference from an antecedent in the next higher clause. Evidence is provided that these embedded clauses are relatively transparent for scrambling and lack independent tense. It is therefore argued that core control verbs in Persian take complements that lack CP, TP, and a Case position for their subjects. Control complements do manifest subject agreement, however, sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…According to Ghomeshi (2001), control verbs in Persian do not form a unified, coherent class, as each verb manifests its own set of idiosyncratic behaviors with respect to tests for control, ranging from marginal to totally acceptable. I will ignore the differences here and restrict the discussion to what Ghomeshi calls core control predicates.…”
Section: Persian Control Constructionsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Ghomeshi (2001), control verbs in Persian do not form a unified, coherent class, as each verb manifests its own set of idiosyncratic behaviors with respect to tests for control, ranging from marginal to totally acceptable. I will ignore the differences here and restrict the discussion to what Ghomeshi calls core control predicates.…”
Section: Persian Control Constructionsmentioning
confidence: 99%
“…According to Ghomeshi (2001), the embedded clause in the construction under discussion is a vP whose specifier contains a null nominal category (about whose grammatical identity she takes no stance). To argue that Persian control verbs take a vP complement, she uses Wurmbrand's (2001) tests based on restructuring and scrambling.…”
Section: Persian Control Constructionsmentioning
confidence: 99%
See 2 more Smart Citations
“…human cognition. Ghomeshi's (2001) study on Persian control and thematic agreement has shown that Persian has core control constructions in which the obligatorily empty subject of an embedded clause takes its reference from an antecedent in the next higher clause. These embedded clauses are relatively transparent for scrambling and lack independent tense.…”
Section: Introductionmentioning
confidence: 99%